Elaine Steinbeck talking with a Man and Woman. - unknown:::creator:::::::::::: (USA; Sag Harbor, New York, 2022)
Elaine Steinbeck talking with unidentified man and woman, possible at the Sag Harbor Old Whalers Festival. Steinbeck, helped sponsor and acted as honorary chairman of the festival. Original is in safe.